2013
DOI: 10.1007/s12010-013-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Association Analysis with Litter Size Traits of Porcine Matrix Metalloproteinase-9 Gene (pMMP-9)

Abstract: The mammalian matrix metalloproteinase-9 (MMP-9), which might play a role in ovulation, uterus remodeling, embryo development, and implantation in mammals, is one of the potential functional candidate genes for porcine reproductive traits. In this study, the entire genomic sequence of porcine MMP-9 (pMMP-9) gene was established; it contains 13 exons and 12 introns. Real-time PCR analysis revealed that pMMP-9 is highly expressed in the Minzhu uterus before puberty and decreases significantly after sexual maturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…MMP-9 is an enzyme that plays a critical role in synaptic plasticity and brain development (Stawarski, Stefaniuk, & Wlodarczyk, 2014). MMP-9 contains 12 introns and 13 exons (Niu, Li, Xiong, & Wang, 2013) and in human MMP-9 comprises 7,654 bases and is located on chromosome 20 (20q11.2-q13.1) (Farina & Mackay, 2014). According to its structure, MMP-9 has many substrates including cell surface receptors, gelatin, growth factors precursors, adhesion molecule, procollagen type II, tissue inhibitors of metalloproteinases (TIMPs) specially TIMP-1, and laminin, which is capable of connecting with them (Bronisz & Kurkowska-Jastrzębska, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 is an enzyme that plays a critical role in synaptic plasticity and brain development (Stawarski, Stefaniuk, & Wlodarczyk, 2014). MMP-9 contains 12 introns and 13 exons (Niu, Li, Xiong, & Wang, 2013) and in human MMP-9 comprises 7,654 bases and is located on chromosome 20 (20q11.2-q13.1) (Farina & Mackay, 2014). According to its structure, MMP-9 has many substrates including cell surface receptors, gelatin, growth factors precursors, adhesion molecule, procollagen type II, tissue inhibitors of metalloproteinases (TIMPs) specially TIMP-1, and laminin, which is capable of connecting with them (Bronisz & Kurkowska-Jastrzębska, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that C − allele has positive effects on egg production and the (−1,954 C + /C − ) polymorphism could be used as a selection marker in chicken breeding to improve laying performance. Comparatively, MMP9 gene polymorphisms were also associated with the litter size traits in pig populations ( Niu et al, 2013 ). Many of the biological aspects of MMP9, including catalytic and non-catalytic activities, as well as specific MMP9 substrates have been implicated in reproduction biology ( Vandooren et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MMP9, TIMP1, SPP1 and POSTN were shown to play a role in regulating fat metabolism and insulin resistance ( 30 , 36 38 ). MMP9, TIMP1, CDC42 and BMP1 were also involved in follicular development ( 39 43 ), suggesting that these proteins may be closely related to pubertal development. However, these proteins had not been previously reported to be related to CPP, and their mechanisms needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%